The Effect of Project Based Learning Model on Creative Thinking Ability - Lavli, Reza Olga Efendi Holan; Efendi, Nur (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2024)
This study aims to determine the effect of the project based learning (PjBL) model on creative thinking skills. This quantitative research was a quasi-experimental design with a non-equivalent control group. The research was conducted on 9th-grade students at Cendikia Junior High School in the academic year 2022/2023, using purposive sampling to obtain 50 students, comprising 25 students in the PjBL class and 25 students in the conventional learning class. The research instrument used was a creative thinking test sheet with indicators of fluency, flexibility, originality, and elaboration. Data analysis used a paired-sample t-test. The research results indicate a significant influence of the PjBL model on creative thinking abilities. There was an improvement in each indicator of creative thinking after implementing PjBL, and the posttest scores achieved were higher than those of students in the conventional learning class. Based on this study, researchers recommend the learning process with a PjBL model to improve creative thinking skills.